Goethes „Erlkönig” als kalter Verführer in transmedialen Umsetzungen - Aadam, Janin (Studia Germanica Posnaniensia, 2015)
The article analyses the presentation of the Erlkönig as a cold seducer in transmedia. In this context, not only the famous ballad of Johann Wolfgang von Goethe from 1782 is regarded, but also transformations in arts, illustrations and especially in film are analysed. Within this regard the violent and coldblooded attitude of the Erlkönig towards the child is focused. In the center of the analysis is the recitation and reception of Goethe’s ballad in Andrew Birkin’s Stefan Zweig-adaptation Burning Secret from 1988. The film expands the poetic source by exposing subtexts such as homoerotic, when the baron von Hau-enstein is presented as a cold seducer like the Erlkönig, who attracts the young Edmund. At the same time Birkin adds another interpretation of the ballad, which doesn’t explain the death of the child as something physical, but as an initiation of becoming an adult and the included desires.